Reprints of Rare Papers on Mollusca: Lefevre and Curtis: Studies on the Reproduction and Artificial Propagation of Fresh-Water Mussels (Continued from Sterkiana 48) - George Lefevre; Winterton C. Curtis (Hello World!, 1972)
In 1912, the United States Bureau of Fisheries published the above paper in the Bulletin, vol. 30 (1910) issued May 10, 1912. In the introduction to the work, the authors, both professors of zoology at the University of Missouri, modestly set forth the results of 'several years' of work during which they had studied the life history of river mussels with the aim of replenishing the beds which had been intensively exploited in the first decade of this century by the demands of the pearl button industry. The authors stated (p.111) that when their data had been analyzed the 'report '.. would constitute one of the most important ecological studies ever made on any group of animals.' The report of Coker, Shira, Clark, and Howard (1921), also published by the U.S. Bureau of Fisheries (voL 37, p. 79-181), bore out that prediction. Sterkiana' s reprinting will appear in several issues, starting with this one, and continue as space is available. (Cont.)